El emprendimiento: un enfoque desde el institucionalismo - Fábregas Rodado, Carlos (Corporación Universitaria Americana, 2018)
This work takes as its structural basis the thematic framework of the theory of institutionalism and its subsequent application as a spearhead for the creation of competitive advantages; entrepreneurship as a scenario for the development of free enterprise and corporate governance as a vital guarantor of the survival of entrepreneurship. Under the above approach, the chapters that make up the work that you have at hand, constitute a coherent plot between theory and practice, with no greater pretension than to generate context and application in the complexity of today's markets, in this, it should be noted that Professor Fábregas succeeds with this fabric of knowledge, with a clear hermeneutics that makes the whole text digestible.